2011
DOI: 10.5012/jkcs.2011.55.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel Analogs of Bortezomib

Abstract: Novel analogs of bortezomib were designed, synthesized and in vitro biological evaluation was carried out using human tumor cell lines A549 and PC3. Docking studies of these analogs of bortezomib was discussed. According to biological investigations, the inhibitors 4, 6, and 8 were found to be more potent than reference drug candidate bortezomib. A549 cell line showed significant sensitivity towards 4, 6, and 8 with IC 50 values 14.03, 18.5, and 12.4 nM, respectively, and PC3 cell line showed IC 50 values 26.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Considering the P 3 position, SAR analysis indicated that only substituents such as 2‐pyrazyl or tetrahydronaphthalen‐1‐yl are beneficial to the potency; small alkyl groups (e.g., CH 3 ) or more hindered groups (e.g., tert ‐butoxy) led to loss of potency. This position has been recently further explored in bortezomib‐like compounds by an Indian research group that obtained derivatives with significant cytotoxicity (nanomolar range) toward human tumor cells A549 and PC‐3 …”
Section: Peptide Boronatesmentioning
confidence: 99%
“…Considering the P 3 position, SAR analysis indicated that only substituents such as 2‐pyrazyl or tetrahydronaphthalen‐1‐yl are beneficial to the potency; small alkyl groups (e.g., CH 3 ) or more hindered groups (e.g., tert ‐butoxy) led to loss of potency. This position has been recently further explored in bortezomib‐like compounds by an Indian research group that obtained derivatives with significant cytotoxicity (nanomolar range) toward human tumor cells A549 and PC‐3 …”
Section: Peptide Boronatesmentioning
confidence: 99%